Supplier selection for the halal instant food and export-oriented industry: a case study using ANP - Putri, Chauliah Fatma; Nugroho, Iwan; Putra, Rangga Pahlevi (Eastern-European Journal of Enterprise Technologies, 2024)
In a competitive business environment, companies must carefully evaluate a range of complex factors to select suppliers that align with operational requirements and market demands. This study employs the Analytic Network Process (ANP) to identify and prioritize critical criteria for supplier selection, including halal certification, quality, sustainability, cost, delivery, flexibility, responsiveness, and technical capabilities. Data were collected through semi-structured interviews with supply chain managers and questionnaire-based surveys, integrating qualitative and quantitative insights. The ANP model was used to analyze the interdependence between these criteria, revealing that quality ranks highest (0.331), followed by halal certification (0.231) and cost (0.157). These findings highlight the priority given to maintaining high product quality and strict adherence to halal standards over short-term cost considerations. Supporting factors such as delivery, flexibility, responsiveness, technical capabilities, and sustainability were also evaluated for their roles in maintaining an efficient supply chain and meeting international logistics requirements. The structured ANP framework provides practical insights for halal instant food manufacturers, enabling them to optimize supply chain management and align with regulatory standards, market demands, and sustainability objectives. This approach enhances export capabilities and strengthens the competitive position of halal food producers in the global market